Development and Analysis of Trajectory Tracking - Othman, Nurul Atikah (2017)
In this project the object moving is used to detect the trajectory tracking. After object moving was be detected in continuous frames it will generate trajectory tracking for the measurement (actual) and prediction (predict) the path of the object moving. Technically, object moving trajectory is the calculating and predict the path of an object image when it moving around in a video scene.